Investigation of lymph node transplantation as therapy for breast cancer related lymphedema - Tobbia, Dalia (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2009)
Humans have hundreds of lymph nodes, collections of which are found in the underarms, groin, neck, chest, and abdomen. They have long been considered 'neutral' elements in terms of lymph transport. An assumption has always been made that the impediment to lymph transport in post-surgical lymphedema is due to lymphatic vessel injury. However, these vessels are damaged routinely in surgical procedures, despite this, post- surgical edema usually resolves over time as the lymphatics regenerate and chronic edema rarely if ever occurs under these circumstances. In contrast, it is clear that the removal of a lymph node or nodes appears to be a prerequisite for lymphedema development especially if this is combined with radiotherapy. Consequently, there is reason to believe that there are other factors that require consideration. In the first instance the aim of the studies reported here was to develop an animal model of post-surgical lymphedema that would permit quantitation of lymphatic transport function after the removal of a single popliteal lymph node in sheep and correlate this with edema formation. Secondly, we used this model to test whether the transplantation of an autologous lymph node into a nodal excision site would restore lymphatic transport function and reduce the magnitude of post-surgical lymphedema.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin